Teknologi Biokompos dalam Biopori vertikal di Kelurahan Pematang Pudu Kecamatan Mandau Kabupaten Bengkalis - Andi Dahliaty; Yuana Nurulita; Titania Tjandrawati Nugroho (Unri Conference Series: Community Engagement, 2021)
Pematang Pudu Village is one of the villages in Mandau District, Bengkalis Regency which is approximately 116 km from Pekanbaru city. Based on information from residents of RT 02 RW 10 Km 5 Jalan Rangau, Pematang Pudu Village often floods. Floods in this area can be caused by overflowing river water, reduced rainwater catchment areas due to construction and land clearing. This biopore infiltration hole is a simple technology that does not require expensive and effective rainwater absorption. In addition, through this technology, it can reduce organic waste and make biocompost to be used as organic fertilizer that can fertilize plants. The purpose of this service activity is to provide knowledge and skills to the community about the benefits of vertical biopore technology and increase public awareness to prevent flooding. The method used in this service activity is the delivery of material using powerpoint media and field practice and involving community members in RT 02 RW 10 Pematang Pudu Village. The results of this service activity show that 38% of socialization participants have a score range between 75-80, 13.66% of socialization participants have a range of values between 85-90, and 28% of socialization participants have a range of values between 95-100. It can be stated that the provision of training has an effect on increasing public knowledge about biopore infiltration holes.